Hadits Scientific: The Wage Integration Paradigm In Sharia Economic Concept - Elman Johari (Journal of Nusantara Economy, 2023)
This study aims to discuss the understanding of scientific hadits including about wages. Research method using descriptive qualitative research method with Content analysis approach which data sources are taken from books, books and scientific  writings from research journals both as primary and secondary sources. The discussion of this research includes hadith about  wages, as well as Islamic economic views on wages. This study concludes that wages  as a basis for synchronized payment of wages are permissible although not mandatory. Because basically the time of payment of wages in Islam there is no provision whether it is moved or terminated until the work is completed. In addition, providing encouragement to help each other so that workers can receive their salaries first before carrying out their work obligations. An important finding in this research is that expediting wage payments is permissible although not mandatory. The context of the hadith means a recommendation, not an obligation. Because basically, in Islam, there is no provision regarding the time for payment of wages, whether it be hastened or terminated until the work is finished.